2021
DOI: 10.3389/fendo.2021.644456
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cumulative Live Birth Rates Between GnRH-A and PPOS in Low-Prognosis Patients According to POSEIDON Criteria: A Cohort Study

Abstract: ObjectiveTo compare the cumulative live birth rate (CLBR) of a gonadotropin-releasing hormone (GnRH) antagonist regimen and a progestin-primed ovarian stimulation (PPOS) regimen in low-prognosis patients according to POSEIDON criteria.DesignSingle-center, retrospective, observational study.SettingHenan Provincial People’s Hospital, Zhengzhou, ChinaPatientsWomen aged ≤40 years, with a body mass index <25 kg/m2, who underwent in vitro fertilization (IVF) or intracytoplasmic sperm microinjection (ICSI) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Details of the endometrial preparation and luteal support procedures used at our center have been described elsewhere ( 24 ). In brief, two methods were prepared, namely, a natural cycle for patients with regular menstrual cycles and a hormone replacement cycle for patients with irregular menstruation (or a history of thin endometrium).…”
Section: Methodsmentioning
confidence: 99%
“…Details of the endometrial preparation and luteal support procedures used at our center have been described elsewhere ( 24 ). In brief, two methods were prepared, namely, a natural cycle for patients with regular menstrual cycles and a hormone replacement cycle for patients with irregular menstruation (or a history of thin endometrium).…”
Section: Methodsmentioning
confidence: 99%
“…Studies by Tang et al 1 also showed that patients with asthenospermia were more likely to use agonist regimens. However, the PPOS regimen increased the normal fertilisation rate compared with the GnRH antagonist protocol 20–22. The above results may prove that in addition to the effects of different ovarian stimulation regimens on the quality of oocytes, there is also a deviation in sperm quality in different protocols.…”
Section: Discussionmentioning
confidence: 83%
“…However, the PPOS regimen increased the normal fertilisation rate compared with the GnRH antagonist protocol. 20–22 The above results may prove that in addition to the effects of different ovarian stimulation regimens on the quality of oocytes, there is also a deviation in sperm quality in different protocols. In the present study, sperm abnormalities were a secondary cause of infertility in LFR patients and sperm motility was even a predictor of LFR.…”
Section: Discussionmentioning
confidence: 88%
“…PPOS in all POSEIDON subgroups and signi cantly higher in Group 4 with POR patients aged ≥ 35 years [12]. However, another study showed no difference in CLBR between PPOS regimen and GnRH-Ant regimen in POR population [13].…”
Section: Methodsmentioning
confidence: 91%
“…The live birth rate (LBR) was the primary outcome. The secondary outcome measures were number of oocytes retrieved, duration of gonadotropin (Gn) treatment, amount of Gn administered, fertilization rates, chemical and clinical pregnancy.PPOS in all POSEIDON subgroups and signi cantly higher in Group 4 with POR patients aged ≥ 35 years [12]. However, another study showed no difference in CLBR between PPOS regimen and GnRH-Ant regimen in POR population [13].In the present study, we retrospectively analyzed the e ciency of the PPOS, GnRH-Ant and GnRH-a protocols for patients in POSEIDON Group 3 with low AMH (< 1.2 ng/mL)/low AFC (< 5 follicles) and less than 35 years old.…”
mentioning
confidence: 89%